Zinc as a Potential Coadjuvant in Therapy for Type 2 Diabetes. Issue 2 (June 2013) - Ruz, Manuel; Carrasco, Fernando; Rojas, Pamela; Codoceo, Juana; Inostroza, Jorge; Basfi-Fer, Karen; Valencia, Alejandra; Vásquez, Karla; Galgani, Jose; Pérez, Alvaro; López, Gloria; Arredondo, Miguel; et al.
Background: Type 2 diabetes is highly prevalent in populations having high rates of overweight and obesity. It is a chronic condition responsible for long-term severe dysfunction of several organs, including the kidneys, heart, blood vessels, and eyes. Although there are a number of pharmacologic products in the market to treat insulin resistance and impaired insulin secretion—the most prominent features of this disease—interventions directed at preserving the integrity and function of β-cells in the long term are less available. The use of some nutrients with important cellular protective roles that may lead to a preservation of β-cells has not been fully tested; among these, zinc may be an interesting candidate. Objective: To assess the potential of zinc supplementation as coadjuvant to diabetes therapy. Methods: This article reviews the available information on the use of zinc as part of diabetes therapy. Results: Cellular and animal models provide information on the insulin mimetic action of zinc, as well as its role as a regulator of oxidative stress, inflammation, apoptosis, and insulin secretion. Zinc supplementation studies in humans are limited, although some positive effects have been reported; mainly, a modest but significant reduction in fasting glucose and a trend to decreased glycated hemoglobin (HbA1c). Conclusions: Zinc supplementation may have beneficial effects on glycemic control. Nevertheless, among the studies considered, the vast majority lasted for 6 months or less, suggesting the importance of conducting long-duration studies given the characteristics of type 2 diabetes as a chronic disease.